Segmentasi Pembuluh Darah pada Citra Retina Menggunakan Ciri Multi-Scale Line Strength - Muhammad Faiz Abdul Hamif; Randy Cahya Wihandika; Agus Wahyu Widodo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
One of the disease that should be worried about and can cause the sufferer to have a risk of complications in several parts of the body is diabetic. If this disease attacked the blood vessel in the eye, this disease then called diabetic retinopathy. Diabetic retinopathy examination is carried out every six months including retinal imaging and analysis. The evaluation of retinal images become a serious burden for opthalmologists because the patients with diabetic retinopathy are increasing but the healthcare workers are limited. One way to alleviate the ophthalmologist's workload is to use computer assistance with Multi-Scale Line Strength algorithm for features extraction and Support Vector Machine (SVM) classification algorithm for segmenting the retinal images in a supervised way and the Optic Disc Exclusion algorithm for eliminating the optic disc area in the segmentation result images. The performance of these algorithm is measured in the DRIVE dataset. The accuracy, sensitivity, and specificity obtained from the Multi-Scale Line Strength algorithm combined with SVM are 0,94021, 0,61084, and 0,99693. If those algorithm is combined with the Optic Disc Exclusion algorithm, the performance results are 0,94014, 0,60277, and 0,99694. Both performance results are obtained at window size 13.